2020
DOI: 10.1111/ejn.14686
|View full text |Cite
|
Sign up to set email alerts
|

How to study anxiety and depression in rodent models of chronic pain?

Abstract: Pain is a multidimensional and subjective experience which is considered as a debilitating disease when it becomes chronic. Chronic pain does indeed affect various aspects of the patient's quality of life, including mood, sleep and cognitive processes (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
100
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(119 citation statements)
references
References 292 publications
(591 reference statements)
0
100
2
1
Order By: Relevance
“…Chronic pain is among the main causes of affective disorders. The same comorbidity among chronic pain and affective disorders is found in animal models of chronic pain [31,32]. Accordingly, anxiety and depression-like behaviors have been widely reported in the SNI model of neuropathic pain [28,[33][34][35][36][37][38][39].…”
Section: Behavioral Symptoms Associated With the Spared Nerve Injurymentioning
confidence: 69%
“…Chronic pain is among the main causes of affective disorders. The same comorbidity among chronic pain and affective disorders is found in animal models of chronic pain [31,32]. Accordingly, anxiety and depression-like behaviors have been widely reported in the SNI model of neuropathic pain [28,[33][34][35][36][37][38][39].…”
Section: Behavioral Symptoms Associated With the Spared Nerve Injurymentioning
confidence: 69%
“…Anxiety and depression are common comorbid emotional deficits that are associated with neuropathic patients that adversely affect the patient's quality of life 28 , 29 . The use of open field and elevated maze plus in the analysis of anxiety-like and depressive behaviour in rodents has been well documented 30 . The study revealed that only a high dose of bromelain was effective in reversing the anxiety-like and depressive-like behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Depressive-like behaviour may require even more time to evolve 66 . Whilst some studies suggest that up to 4 months may be required before robust anxiety-behaviour is evident after injury 14,15 , other studies using similar methodology have not replicated these observations 16 , perhaps as a consequence of animal-related factors such as strain or gender 25 . To our knowledge, very few studies have explored the effect of strain on the development of emotional comorbidities after nerve injury 44 .…”
Section: Discussionmentioning
confidence: 99%
“…And despite very similar methodology, some preclinical studies show time-dependent development of anxiety-like comorbidity following nerve-injury 14,15 , while others have failed to confirm this 16 , where the only apparent differences have been animal-and facility-related factors, like strain, gender and laboratory environment. A broad range of studies have now compared different inbred and outbred rat strains on parameters related to pain, anxiety and depression (examples: [17][18][19][20][21][22][23][24] ), but surprisingly, to our knowledge, very few have explored the effects of strain/animal genetics on the development of emotional comorbidities following injury, despite assumptions that this may be a relevant factor to explain the variability in the field 25 .…”
mentioning
confidence: 99%